Bitter taste receptor agonists alter mitochondrial function and induce autophagy in airway smooth muscle cells - Pan, Shi (Am J Physiol Lung Cell Mol Physiol, 2017)
Airway remodeling, including increased airway smooth muscle (ASM) mass, is a hallmark feature of asthma and COPD. We previously identified the expression of bitter taste receptors (TAS2Rs) on human ASM cells and demonstrated that known TAS2R agonists could promote ASM relaxation and bronchodilation and inhibit mitogen-induced ASM growth. In this study, we explored cellular mechanisms mediating the antimitogenic effect of TAS2R agonists on human ASM cells. Pretreatment of ASM cells with TAS2R agonists chloroquine and quinine resulted in inhibition of cell survival, which was largely reversed by bafilomycin A1, an autophagy inhibitor. Transmission electron microscope studies demonstrated the presence of double-membrane autophagosomes and deformed mitochondria. In ASM cells, TAS2R agonists decreased mitochondrial membrane potential and increased mitochondrial ROS and mitochondrial fragmentation. Inhibiting dynamin-like protein 1 (DLP1) reversed TAS2R agonist-induced mitochondrial membrane potential change and attenuated mitochondrial fragmentation and cell death. Furthermore, the expression of mitochondrial protein BCL2/adenovirus E1B 19-kDa protein-interacting protein 3 (Bnip3) and mitochondrial localization of DLP1 were significantly upregulated by TAS2R agonists. More importantly, inhibiting Bnip3 mitochondrial localization by dominant-negative Bnip3 significantly attenuated cell death induced by TAS2R agonist. Collectively the TAS2R agonists chloroquine and quinine modulate mitochondrial structure and function, resulting in ASM cell death. Furthermore, Bnip3 plays a central role in TAS2R agonist-induced ASM functional changes via a mitochondrial pathway. These findings further establish the cellular mechanisms of antimitogenic effects of TAS2R agonists and identify a novel class of receptors and pathways that can be targeted to mitigate airway remodeling as well as bronchoconstriction in obstructive airway diseases.